Optimizing Sunspot Forecasts: An In-Depth Analysis of the ConcaveLSTM Model - I Wayan Ordiyasa; Mohammad Diqi; Marselina Endah Hiswati; Aulia Fadillah Wani Wandani (International Journal of Informatics Engineering and Computing, 2025)
This work examines how effectively the ConcaveLSTM model can forecast sunspot numbers, recognizing their importance in space weather. The model addresses the complex and changing sunspot characteristics to improve forecasting accuracy. By comparing different model variations, this research identifies optimal combinations of input steps and LSTM units that enhance forecast performance while avoiding overfitting. The study showcases the capability of specific architectures concerning detail versus computational cost, using evaluation metrics such as RMSE, MAE, MAPE, and R2. Considering factors like limited data availability and the complexity of solar phenomena, the ConcaveLSTM model could be a valuable tool for predicting solar activity. This research advances understanding of space weather forecasting through machine learning and offers guidance for further model development and future investigations.